Optimization for Production Tert-Butyl Oleyl Glycoside Nonioic Surfactant Using Response Surface Methodology - Harsa Pawignya; Tutuk Djoko Kusworo; Bambang Pramudono (ASEAN Journal of Chemical Engineering, 2019)
The development of surfactant production process strongly influenced by the potential use of raw materials and products that are environmentally friendly. For raw materials such as surfactants are carbohydrate-based material utilization example, glucose, which is reacted with tert-butanol, to form tert-butyl glycoside (TBG), then TBG can be esterified with oleic acid forming surfactant tert-butyl oleyl glycoside (TBOG). This study aims to obtain the optimum conditions TBOG production process of esterification reactions TBG and oleic acid catalyst the para toluene sulfonic acid using response surface method to reach optimum yield TBOG. The independent variable used is the mole ratio of TBG with oleic acid, percent of the catalyst and a temperature. Optimization results obtained optimum conditions of mole ratios of 1: 4.096; 2.33 percent of the catalyst and the temperature of 96.04 °C with a TBOG yield of 92.46%, with a TBOG content of 91.72 %. Based on the HLB value of the surfactant TBOG is 3.87, then these surfactants can be used as an emulsifier of water-in-oil.